Peran Etika Periklanan Dalam Mencegah Iklan yang Menyesatkan - Dea Zhafira Widyaningsih; Dinni Sabrina Bahri; Daniel Handoko (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
This study aims to examine the role of advertising ethics in preventing misleading advertisements in the increasingly digital era. The research method used is descriptive qualitative, utilizing literature review and document analysis. Data were collected through the analysis of relevant documents such as journal articles, books, research reports, advertising regulations, and industry codes of ethics. The findings indicate that advertising ethics principles, such as truthfulness, honesty, transparency, social responsibility, and respect for consumers, are crucial in maintaining the integrity of the advertising industry and protecting consumers from false or deceptive information. Additionally, effective oversight and regulation mechanisms by regulatory bodies like the FTC and ASA play a crucial role in enforcing these ethical standards. The study recommends developing new ethical standards to accommodate technological advancements and modern advertising practices to ensure advertisements remain fair and responsible.